Цэргийн үлээвэр хөгжмийн хөгжлийн асуудал - Цогтгэрэл, Ш. (Historia Mongolarum, 2009)
This article tells about a history of use wind music in military actions, about revival of the first wind orchestra in Mongolia, how was created a state hymn of Mongolia at Bogdo khan, about a role of a wind orchestra in the Mongolian culture and defensive business. Also it considers features of development of a military wind orchestra of Mongolia from the point of view of a history.